Bordetella effector BopN is translocated into host cells via its N‐terminal residues. (13th June 2017) - Abe, Akio; Nishimura, Ryutaro; Kuwae, Asaomi
ABSTRACT: Bordetella bronchiseptica infects a wide variety of mammals, and the type III secretion system (T3SS) is involved in long‐term colonization by Bordetella in the trachea and lung. T3SS translocates virulence factors (commonly referred to as effectors) into host cells, leading to alterations in the host's physiological function. The Bordetella effectors BopN and BteA are known to have roles in up‐regulation of IL‐10 and cytotoxicity, respectively. Nevertheless, the mechanism by which BopN is translocated into host cells has not been examined in sufficient detail. Therefore, to determine the precise mechanisms of the BopN translocation into host cells, we built truncated derivatives of BopN and evaluated the derivatives' ability to translocation into host cells by adenylate cyclase‐mediated translocation assay. It was found that N‐terminal amino acid (aa) residues 1–200 of BopN are sufficient for its translocation into host cells. Interestingly, BopN translocation was completely blocked by deletion of the N‐terminal aa residues 6–50, indicating that the N‐terminal region is critical for BopN translocation. Furthermore, BopN appears to play an auxiliary role in BteA‐mediated cytotoxicity. Thus, BopN can apparently translocate into host cells and may facilitate activity of BteA.